The Status and Function of Intellectuals in State and Society in India and China: Some Critical Comparisons - V. Subramaniam (International Sociology 1987; 2; 301, 1987)
Abstract Max Weber's comparative studies of the great non-European civilisations of India, China and Islam were, in spite of their breadth of content, focussed on the problem of the non-evolution of modern capitalism in them and most Webenan scholars did not, unfortunately, move far away from this. But the most mteresting topic of companson between China and India is not their common non-generation of capitalism but the totally different relation that evolved between the intellectuals and the state in each. A collaborative relation of the literati in the service of the state was evolved in China by the Han dynasty by a clever distortion of the Confucian ethic and it lasted with minor discontinuities until early this century. By contrast, the Indian Brahmin intellectuals gave only conditional support to the State, treating Dharma or Universal law as supreme and gave up hope of the impenal integration of India by the seventh century. Instead, they built a flexible pattern of cultural integration - based on Bhakti for contact with the masses and an all-India cultural elite for leadership - which has lasted all these centuries.